Natural killer cell: New suspect on cytokine storm in COVID-19 infection: Natural killer cell: New suspect on cytokine storm - Chegni, Hamid; Rahmani-Kukia , Nasim; Abbasi, Ardeshir; Pakravan, Nafiseh; Pourshaban, Manoochehr; Mohammad hasan, Zuhair (Archives of Advances in Biosciences, 2021)
Context: Various studies show that contracting the Covid 19 disease can affect the normal functioning of the immune system. In some patients, lack of stimulation of the specific immune system causes excessive innate immune activity and secretion of inflammatory cytokines. Evidence Acquisition: It seems that the occurrence of cytokine storm depends on various factors. One of the immune system cells that can play an important role in cytokine storm is Natural killer (NK) cell. Thus, more attention should be paid to the role of NK cell in patients with Covid-19. Results: In this article, we seek to examine the role of NK cell in cytokine storms. Conclusion: Perhaps the difference between the characteristics of NK cell in children and adults is due to the difference in the severity of symptoms after infection with Covid-19.